2018
DOI: 10.1108/jsm-01-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Etourism advertising effectiveness: banner type and engagement as moderators

Abstract: Purpose This paper aims to analyze advertising effectiveness in terms of self-reported memory (recall) by measuring customers’ visual attention, including consumer engagement with e-tourism 2.0 tools and the banner type used as moderating variables. Design/methodology/approach Data were collected through a within-subject, between-groups experimental design based on eye-tracking methodology, followed by a self-administered questionnaire. Participants were instructed to visit three e-tourism tools, namely, a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…To achieve this goal, the interaction between the banner's features and user's characteristics will be objectively examined in an experimental environment, using the eyetracking methodology to capture selective visual attention (Geise, 2012) and complemental SJME self-reported measures of memory (Hern andez-Méndez and Muñoz-Leiva, 2015). Recent studies have analysed the advertising effectiveness, measuring the visual attention to the ads with a similar methodological approach (Flavi an et al, 2011;Muñoz-Leiva et al, 2018;Simmonds et al, 2020aSimmonds et al, , 2020b.…”
Section: Mediating Role Of Visual Attentionmentioning
confidence: 99%
“…To achieve this goal, the interaction between the banner's features and user's characteristics will be objectively examined in an experimental environment, using the eyetracking methodology to capture selective visual attention (Geise, 2012) and complemental SJME self-reported measures of memory (Hern andez-Méndez and Muñoz-Leiva, 2015). Recent studies have analysed the advertising effectiveness, measuring the visual attention to the ads with a similar methodological approach (Flavi an et al, 2011;Muñoz-Leiva et al, 2018;Simmonds et al, 2020aSimmonds et al, , 2020b.…”
Section: Mediating Role Of Visual Attentionmentioning
confidence: 99%
“…Some other studies investigate the impact of demographic and travel characteristics of hotel guests on online and offline reservations (Crnojevac et al, 2010; Golmohammadi et al, 2017; Pitoska, 2013; Ruiz-Gómez et al, 2018). Recently, the works analyzing the importance of online reviews and advertising in the choice of accommodation have acquired great relevance (Bronner and de Hoog, 2011; Filieri and McLeay, 2014; Muñoz-Leiva et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The academic literature shows an increasing number of studies using eye-tracking as well as its strong ability to assess the effectiveness of visual marketing [39][40][41][42]. While eye tracking offers information that cannot be obtained with traditional techniques, it also complements traditional techniques by providing more detail [39].…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Attitude was measured on a five-point Likert scale adapted from Tang et al [50], recall was measured with an open question and suggested recall with a screening question [41]. The screening question was: "what did the message(s) you remember consist of?"…”
Section: Measurement Scalesmentioning
confidence: 99%
See 1 more Smart Citation